2021
DOI: 10.1136/postgradmedj-2020-139182
|View full text |Cite
|
Sign up to set email alerts
|

Planning virtual residency interviews as a result of COVID-19: insight from residency applicants and physicians conducting interviews

Abstract: BackgroundIn response to the COVID-19 pandemic, the 2020–2021 residency interview process will undergo significant changes. Residency programme stakeholders would benefit from knowledge on what students and physicians expect from this process.ObjectiveThe purpose of the study was to describe and contrast the perspectives of student applicants and interviewing physicians related to the residency programme virtual interview process.MethodsA survey consisting of 24 Likert statements was administered across listse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 7 publications
0
39
1
Order By: Relevance
“…Several studies have examined the complete transition to virtual interviews during the pandemic for training programs from a variety of medical specialties [5][6][7][8][9][10][11]. As remote interviews may become commonplace following resolution of the pandemic, it is important to evaluate both programs' and applicants' perspectives on using virtual platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the complete transition to virtual interviews during the pandemic for training programs from a variety of medical specialties [5][6][7][8][9][10][11]. As remote interviews may become commonplace following resolution of the pandemic, it is important to evaluate both programs' and applicants' perspectives on using virtual platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Applicants’ priorities include assessing a program's culture, often through informal interactions, in addition to presenting themselves in the best light possible, which some feel is hampered by the virtual format. 6 , 22 , 23 Likewise, some programs have expressed dismay at the difficulty in assessing an applicant's “fit” and surgical aptitude. 24 , 25 - 26 …”
Section: Virtual Interviewsmentioning
confidence: 99%
“…Gender differences did not significantly impact the applicants’ perceptions, as was also the case in Baker et al (2020) and Seifi et al (2020) . But Shreffler et al (2021) found that male and female applicants differed regarding their responses to some survey statements. At the time of this study, 75% of our participants did not have any prior experience with VI.…”
Section: Discussionmentioning
confidence: 96%
“…The same changes in interview processes for recruitment purposes occurred in other educational sects, especially medical education, which was highly impacted by the pandemic ( Bhardwaj et al, 2021 ) including recruiting medical students for residency ( Davis et al, 2020 ; Foong, 2020 ; Shreffler et al, 2021 ), surgical training ( Day et al, 2020 ; McKinley et al, 2020 ), and emergence medicine ( Deiorio et al, 2019 ). The United States health care is dramatically impacted by the pandemic ( Patel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%